Implementation of Failover on Mikrotik Router using Check Gateway and Distance Parameters - Jayadi, Akhmad; Sadamaputra, Frendy (PT. Lontara Digitech Indonesia, 2023)
At the end of 2019 the world faced the Covid 19 Virus pandemic which also changed activities in daily life. All activities are carried out at home (Work From Home) including meetings and exchanging information via digital. Problems at this time in the office of PT. PLN often loses internet connection, at PT. PLN ULTG Tarahan also uses 2 ISP (Internet Service Provider) lines Indihome and Icon Plus in the server room, there is no system that can regulate the two ISP networks so that they can switch connection lines if there is a disturbance on the main ISP line so that there is a possibility of interruption during activities using the internet network. Failover is a technique for adding connections in Mikrotik, where if one of the internet connections dies (main connection), the other connection (backup connection) will replace the main connection line by defining a check gateway and differentiating the distance value on each routing rule. The results of this study will be able to guarantee the availability of internet at the PT. PLN ULTG Tarahan so as to increase employee productivity.